0.18µm Teknolojisinde Birinci Ve Üçüncü Kuşak Akım Taşıyıcılar İle Yeni Olanaklar - Gonca, Oğuz (Fen Bilimleri Enstitüsü, 2014)
Akım modlu devreler ve akım taşıyıcı gibi akım modlu devre elemanları son yıllarda birçok çalışmaya konu olmuşlardır. Akım modlu devre elemanlarına karşı giderek artmakta olan bu ilgi, akım modlu devre elemanlarının işlemsel kuvvetlendirici gibi gerilim modlu devre elemanlarına göre daha iyi lineerlik ve daha iyi band genişlikleri sağlamasından kanaklanmaktadır. Buna paralel olarak akım modlu süzgeçler, gerilim modlu benzerlerine göre daha geniş dinamik sınırlar ve daha büyük band genişlikleri sunabilmektedirler. Düşük giriş empedansları ve yüksek çıkış empedanslarına sahip akım modlu süzgeçler, herhangi bir ek aktif elemana ihtiyaç duyulmaksızın, ard arda bağlanarak daha yüksek seviyeli süzgeçler ve osilatörler elde edilebilmektedir. Bu tez çalışmasında, genel olarak her kuşak akım taşıyıcı yapısına değinilmiş, yapıların çalışma şekilleri, tanım bağıntınları ortaya konulmuştur. Ayrıca bir kuşaktan diğerini geçekleştirme yötemlerine yer verilmiştir. Ağırlıklı olarak Birinci Kuşak Akım Taşıyıcılar (CCI) ve Üçüncü Kuşak akım taşıyıcılar (CCIII) ele alınmış ve daha iyi lineerlik için farklı giriş katları daha esnek çıkış kazançları için yeni elemanlar önerilmiştir. Bölüm 1’de konuya genel bir giriş yapılmış, tez çalışmasınında nelerin amaçlandığından bahsedilmiş ve literatürde şimdiye kadar yapılmış olan çalışmalara yer verilmiştir. Bölüm 2’de akım taşıyıcıların genel özellikleri ortaya konulmuştur. Ayrıca birinci, ikinci ve üçüncü kuşak akım taşıyıcı yapıları ayrıntılarıyla incelenmiş buna ek olarak Elektronik Olarak Kontrol Edilebilen İkinci Kuşak Akım Taşıyıcı (ECCII) yapısına ve  Değiştirilmiş Üçüncü Kuşak Akım Taşıyıcı (MCCIII) yapılarına yer verilmiştir. Kuşaklar arası dönüşüm yöntemleri de bu bölüm içerisinde yer almaktadır.  Bölüm 3’te CCI ve CCIII için iç yapılar önerilmiş ve bu yapılar giriş ve çıkış eşitlikleriyle incelenmiştir. Bölüm 4’te gerçekleştirilen CCI ve CCIII yapıları için benzetimler sonucunda elde edilmiş olan karakteristik eğrileri verilmiştir. Bölüm 5’te CCI ve CCIII yapılarının kullanılabileceği uygulama devrelerinden örnekler verilmiş ve devre yapıları incelenmiştir. Ayrıca devrelerin SPICE benzetim sonuçları sunulmuştur. Bölüm 6’da elde edilen sonuçlar değerlendirilmiş ve tezin amacına ne kadar yaklaştığı gerekçeleriyle ortaya konulmuştur.

In the last years, current mode circuits and current mode circuit elements like current conveyors have been subject to many studies. Interest on current mode circuit elements increases every passing day because of their better linearity and wider bandwidth than the voltage mode circuit elements. In the same way, current mode filters also provide wider dynamic ranges and wider bandwidths than the similar voltage mode filters. Furthermore, current mode filters give better possibilities to build high order filters or oscilators by use of cascade filter connections because of their low input impedances and high output impedances. Current Conveyor structure (Current Conveyor, CC) was first introduced in 1968 by Smith and Sedra and it took an important place in our lives as an important new circuit element. Definition relations of the current conveyor generations are includes very small but important differences. Sedra and Smith introduced “Second Generation Current Conveyor” with changes made in definition relations two years later in 1970. And the last member of the generations "Third Generation Current Conveyor (CCIII)" is presented by Fabre in 1995. In this study, the overall structures of each generation current conveyor is mentioned, the structure of the way it works, the definition of relations have been introduced. Also methods to achive from one generation to the other is given. Mainly the first generation current conveyors (CCI) and the Third Generation Current Conveyors (CCIII) discussed and different input types for better linearity, new elements for more flexible output gains have been proposed.  Introduction, literature research and purpose of this thesis are mentioned in        Chapter 1. In Chapter 2, the general features of the current carriers have been introduced. Also a First Generation Current Conveyor, Second Generation Current Conveyor and Third Generation Current Conveyor structures were examined in detail. Electronically Controllable Second Generation Current Conveyor (ECCII) structure and the Modified Third Generation Current Conveyor (MCCIII) structures are given. Inter-generational transformation methods are included in this section. In Chapter 3, CCI and CCII internal structures have been proposed and these structures were studied with input and output equation. In this chapter eight different internal structure is given and two of them Electronically Controllable First Generation Current Conveyor (ECCI) and Electronically Controllable Third Generation Current Conveyor (ECCIII) are new elements that we introduced in this thesis study. In Chapter 4,  • Current conduction characteristics,  • VX-VY voltage monitoring characteristics,  • (VZ + ,VZ-)-VY characteristics,  as DC characterizations, • VX / VY voltage monitoring frequency response, • The frequency response of current gains, • The frequency response of ZX impedance • The frequency response of ZY impedance • The frequency response of ZZ+ impedance • The frequency response of ZZ- impedance as AC characterizations of CCI’s and CCIII’s are given, by means of simulation results.  In Chapter 5,  • All-pass filters with CCI’s, • All-pass filters with CCIII’s, • Lossy grounded inductance simulation and low-pass high-pass filter with CCIII’s,  • Inductance simulation and the universal filter with MCCIII’s, • Adjustable amplitude resonance circuit with ECCIII  as application circuits and the frequency response of current gains and current phase frequency curves of all-pass filters, frequency response of inductance and the frequency response of current gain for low-pass high-pass filters, frequncy response of inductance and frequncy response of current gain for universal filters and tansient curves of output current for adjustable amplitude resonance circuit with ECCIII in two different resonance frequency as their SPICE smiulation results are given. In Chapter 6, the results obtained are evaluated and how close to the purpose of the thesis on grounds that have been introduced. In this study, differences of current conveyor generations, each other conversion methods between generations, improvement of voltage and current tracking with different input stages, obtaining electronically controllable output current gain with different output stages is emphasized.  0.18μm technology to be realized in the current circuits, improvement of working conditions with the additions made and control the earning ratios easily were studied. Low power consumption of current-mode circuits and be open to integration and the facilities operating at high frequencies with the CMOS structures manufactured in appropriate processes increasing the orientation to these structures. In this study, elements that have been proposed ECCI and ECCIII provides control the output gain and it is quite easy to create new circuit topologies with these facilities. The circuit structures functioning in new technologies and the effectiveness of the proposed structure is illustrated by application circuits. The results obtained from simulations are noteworthy that how close to ideal. All of the simulations reveal that operating ranges and results close to ideal,  validity of methods and structures used in the study have shown again.
New Possibilities With First And Third Generation Current Conveyors In 0.18μm Technology
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2014
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2014
Keywords: Akım Taşıyıcı; Birinci Kuşak Akım Taşıyıcı; Üçüncü Kuşak Akım Taşıyıcı; Current Conveyor; First Generation Current Conveyor; Third Generation Current Conveyor